Students' Expression of Admiration for Science Experiments in Elementary School Classes - Nirwati, Nirwati; Katmas, Hamimah (IAIN Sorong, 2023)
Abstract This research explores students' expressions of admiration for science experiments at the elementary school level with the aim of understanding the dynamics and factors that influence students' emotional responses to science experiment activities. The research method involved observing facial expressions, verbal behavior, and audiovisual recordings during the implementation of science experiments in several elementary school classes. In addition, data was collected through interviews and questionnaires to get direct views from students regarding their admiration for science experiments. The results showed that students consistently expressed high levels of admiration for science experiments. Factors such as interest in the learning material, interaction with the teacher, and students' level of involvement in the experimental process play an important role in shaping their expressions of admiration. In addition, this research also identified different patterns of emotional expression depending on student characteristics, such as age level and individual interest in science. These findings contribute to our understanding of students' emotional responses to science experiment activities in elementary schools. The implications can be used to design learning strategies that are more interesting and effective in increasing students' admiration for natural science. Additionally, this study also opens the door for further research into the role of emotions in science learning and how these positive experiences can translate into increased students' understanding and interest in science.